A monocentric phase I study of vemurafenib plus cobimetinib plus PEG-interferon (VEMUPLINT) in advanced melanoma patients harboring the V600BRAF mutation - Simeone, Ester; Scognamiglio, Giosuè; Capone, Mariaelena; Giannarelli, Diana; Grimaldi, Antonio M.; Mallardo, Domenico; Madonna, Gabriele; Curvietto, Marcello; Esposito, Assunta; Sandomenico, Fabio; Sabbatino, Francesco; Bayless, Nicholas L.; et al. (Journal of translational medicine, 2021)
Studies carried out in vitro and in a mouse model have shown that BRAF inhibitors enhance the effects of IFN-α on BRAFV600E melanoma cells through the inhibition of ERK. Therefore, the combination of vemurafenib and IFN-α in patients with BRAFV600E melanoma may provide therapeutic benefits; MEK inhibition may prevent the reactivation of the MAPK pathway induced by BRAF inhibitor resistance. In a phase I study, adult patients with advanced BRAFV600-mutated melanoma were treated with vemurafenib + PEG-IFN-α-2b or vemurafenib + cobimetinib + PEG-IFN-α-2b, to assess the safety of the combination and the upregulation of IFN-α/β receptor-1 (IFNAR1). Eight patients were treated; 59 adverse events with four serious ones (three related to study treatments) were reported. Patients with a pre-treatment IFNAR1 expression on ≤ 35% melanoma cells had a median progression-free survival of 12.0 months (range: 5.6-18.4 months) and a median overall survival of 31.0 months (range: 19.8-42.2 months), while patients with a pre-treatment IFNAR1 expression on > 35% of melanoma cells had a median progression-free survival of 4.0 months (range: 0-8.8; p = 0.03), and a median overall survival of 5 months (p = 0.02). Following treatment, responders had higher levels of growth-suppressor genes, including GAS1 and DUSP1, and genes involved in a metabolically robust immune response, including FAP. Our study supports the overall safety of the vemurafenib + PEG-IFN-α-2b + cobimetinib combination. IFNAR1 expression levels correlated with response to treatment, including survival. Vemurafenib + PEG-IFN-α-2b + cobimetinib would have difficulty finding a niche in the current treatment scenario for advanced melanoma, but we speculate that our findings may contribute to identify subjects particularly responsive to treatment. The study was registered at clinicaltrials.gov (NCT01959633). Registered 10 October 2013, https://clinicaltrials.gov/ct2/show/NCT01959633.